English Movies Increase Students’ Speaking Scores in Vocational High School - Gatycha Allar Dezaurna Darmawan; Dian Rahma Santoso (Academia Open, 2025)
General Background: Speaking is a complex language skill requiring accurate pronunciation, vocabulary, fluency, and confidence for meaningful communication in English as a foreign language. Specific Background: Many high school students experience limited exposure to authentic language input and insufficient opportunities for oral practice, resulting in low speaking performance. Knowledge Gap: Although audiovisual media are widely used, empirical evidence on short English movies as classroom media in vocational high schools remains limited. Aims: This study investigated whether English movies could improve students’ speaking ability in a tenth-grade accounting class at a vocational high school. Results: Using a quantitative pre-experimental one-group pre-test–post-test design with 38 students, the average score increased from 69.47 to 90.26, a gain of 20.79 points, supported by a paired-sample t-test showing a statistically significant difference (p < 0.001). Improvements were observed in pronunciation, vocabulary, fluency, motivation, and confidence during speaking tasks. Novelty: The study demonstrates the pedagogical value of short subtitled English films integrated with recount-text retelling activities in a real classroom setting. Implications: English movies can serve as engaging audiovisual media that promote active participation, provide authentic language exposure, and support communicative competence development in secondary EFL instruction. Highlights: Mean performance rose by 20.79 points between initial and final assessment. Learners displayed greater confidence and participation during oral tasks. Subtitled short films supported clearer pronunciation and richer vocabulary use. Keywords: English Movies; Speaking Ability; Audiovisual Media; EFL Learners; Vocational High School